Students’ Perceptions of the Quality of High-Speed Sewing Machines in the Workshop at SMK Negeri 8 Padang - Wari, Felmi; Nelmira, Weni (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
This study was conducted to determine the quality of high-speed sewing machines in the workshop of the Fashion Design Department of SMK Negeri 8 Padang. This descriptive quantitative study was performed using percentage analysis and categorization. The population included all 11th and 12th-grade students enrolled in the July-December 2023 semester, out of which 80 students were selected as samples using the simple random technique. A set of 5-point Likert scale questionnaires was used to collect the data. The results showed that five students (6.25%) perceived the quality of high-speed sewing machines as very high in terms of damage, while 25 students (31.25%) perceived it as high, and 30 others (37.5%) found it moderate. Furthermore, 17 students (21.25%) perceived that the damage to the machine was low, and 3 others (3.75%) categorized it as very low. Six students (7.5%) categorized care and maintenance as very high, and 11 (13. 75%) found it high. 18 students (22.5%) categorized the care and maintenance of the high-speed sewing machine as moderate, and 38 students (47.5%) categorized it as low. The remaining seven students (8.75%) perceived it within the low category.